2020
DOI: 10.2147/dmso.s266589
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of Adherence to Self-Care Behavior Among Patients with Diabetes at Public Hospitals in West Ethiopia</p>

Abstract: Background: Diabetes is a typical chronic disease that needs integrated and multifaceted approaches. Self-care practices are fundamental to achieve good blood glucose control and prevent long-term complications. Therefore, the aim of the study was to determine the level and predictors of adherence to self-care behavior among patients with diabetes on follow-up at public hospitals of western Ethiopia. Patients and Methods: The cross-sectional study design was employed on a sample of 423 diabetic patients on fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
2
12
1
Order By: Relevance
“…This study revealed that 60.4% of study participants had poor self-care practices. This finding was in line with the study conducted in central Tigray hospital 62.7% [ 27 ], and west Ethiopia at 57.3% [ 28 ]. However, this finding was higher than a study conducted at Debre Tabor University 36.9% [ 29 ], in Addis Ababa Ethiopia 52% [ 30 ], Jimma medical center 45.8% [ 31 ], in Tigray 53.3% [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that 60.4% of study participants had poor self-care practices. This finding was in line with the study conducted in central Tigray hospital 62.7% [ 27 ], and west Ethiopia at 57.3% [ 28 ]. However, this finding was higher than a study conducted at Debre Tabor University 36.9% [ 29 ], in Addis Ababa Ethiopia 52% [ 30 ], Jimma medical center 45.8% [ 31 ], in Tigray 53.3% [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…[ 20 ] Self-efficacy of diabetes was determined basing on the 7 domains of diabetes self-management as described previously. [ 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…The long-term maintenance of the positive impact of education activities is still up for debate, although longer-term effects are shown in patients who participated in group education programs 24 . In these patients, there is evidence of signi cant results, such as better glycaemic control, increased knowledge about diabetes, self-management skills, and selfe cacy/empowerment 25 .…”
Section: Discussionmentioning
confidence: 99%